Measurements of direct CP-violating asymmetries in charmless decays of bottom baryons. - Aaltonen, T; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Arisawa, T; Artikov, A; Asaadi, J; Ashmanskas, W; et al. (2014)
We report final measurements of direct CP-violating asymmetries in charmless decays of neutral bottom hadrons to pairs of charged hadrons with the upgraded Collider Detector at the Fermilab Tevatron. Using the complete √s=1.96  TeV proton-antiproton collisions data set, corresponding to 9.3  fb⁻¹ of integrated luminosity, we measure A(Λ(b)⁰→pπ⁻)=+0.06±0.07(stat)±0.03(syst) and A(Λ(b)⁰→pK⁻)=-0.10±0.08(stat)±0.04(syst), compatible with no asymmetry. In addition we measure the CP-violating asymmetries in B(s)⁰→K⁻π⁺ and B⁰→K⁺π⁻ decays to be A(B(s)⁰→K⁻π⁺)=+0.22±0.07(stat)±0.02(syst) and A(B⁰→K⁺π⁻)=-0.083±0.013(stat)±0.004(syst), respectively, which are significantly different from zero and consistent with current world averages.